2021
DOI: 10.1038/s41598-020-80855-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PET data driven respiratory motion correction and BSREM reconstruction of 68Ga-DOTATATE PET/CT for differentiating neuroendocrine tumors (NET) and intrapancreatic accessory spleens (IPAS)

Abstract: To evaluate whether quantitative PET parameters of motion-corrected 68Ga-DOTATATE PET/CT can differentiate between intrapancreatic accessory spleens (IPAS) and pancreatic neuroendocrine tumor (pNET). A total of 498 consecutive patients with neuroendocrine tumors (NET) who underwent 68Ga-DOTATATE PET/CT between March 2017 and July 2019 were retrospectively analyzed. Subjects with accessory spleens (n = 43, thereof 7 IPAS) and pNET (n = 9) were included, resulting in a total of 45 scans. PET images were reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…2-Deoxy-2-[18F]fluoro-D-glucose positron emission tomography/computed tomography ([ 18 F]FDG PET/CT) is typically used for the staging and restaging of high-risk melanoma patients, mainly for the detection of lymph node metastases and distant metastases. With the advent of digital PET and novel iterative reconstruction techniques, the detectability of small-sized [ 19 ] and faintly [ 18 F]FDG-avid lesions has improved considerably [ 20 , 21 ]. Hence, digital PET/CT may play a relevant role in the detection of the exact number, size, and location of ITM and may subsequently impact patient management and therapy-related decisions [ 18 , 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…2-Deoxy-2-[18F]fluoro-D-glucose positron emission tomography/computed tomography ([ 18 F]FDG PET/CT) is typically used for the staging and restaging of high-risk melanoma patients, mainly for the detection of lymph node metastases and distant metastases. With the advent of digital PET and novel iterative reconstruction techniques, the detectability of small-sized [ 19 ] and faintly [ 18 F]FDG-avid lesions has improved considerably [ 20 , 21 ]. Hence, digital PET/CT may play a relevant role in the detection of the exact number, size, and location of ITM and may subsequently impact patient management and therapy-related decisions [ 18 , 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature documents many case reports of false positives on PET-CT NETSPOT due to ectopic splenic anomalies [12][13][14][15][16][17]. One case report with a literature review showed that 66.7% of patients with intrapancreatic accessory spleen ended up undergoing unnecessary pancreatic resections [13].…”
Section: Discussionmentioning
confidence: 99%
“…While this technique could have been utilized for our patient, a biopsy was performed in lieu of other available techniques. A study by Liberini et al showed that utilization of motion correction factors in PET/CT and high standard uptake value (SUV) cut-off (suggested at 42) can also help distinguish NETs from ectopic splenic anomalies [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the vendor tools provide fully automated workflows that culminate with a 'simple' final 3D motion-corrected image. Using these tools, we are already seeing a new research arena with large patient cohorts being studied [44,46,51,55], providing statistical power to demonstrate a desirable evolution of quantitative and qualitative PET through the use of DDMC. Encouragingly, we are also seeing research studies branching out beyond the traditional PET motion correction focus of lung lesion quantification to address additional clinical applications, such as cardiac imaging and diagnostic tumour/organ differentiation [47,48,55,56].…”
Section: Motion Correction In Petstanding At the Edge Of A Paradigm Shiftmentioning
confidence: 99%